Mechanical Properties of Polyvinyl Chloride Plastics Recycled Aggregate Concrete - A. Al-Azzawi, Adel; S. Shalal, Mustafa (International Journal of Engineering and Technology, 2018)
The concrete prepared with Polyvinyl chloride plastics (collected from doors and windows wastes) as recycled coarse aggregates and their concrete engineering properties are studied in the laboratory in this research. The concrete blends have an expected cylinder compressive strength of 28 MPa. In this research, the concrete blends contain plasticcoarse aggregate.The ratio of this aggregate to the total aggregate volume ranges from 0 to 1. The concrete strength properties in tension and compression are greatly affected with the plastic replacement ratio. The blends density reduces with increasing replacement ratio. For low replacement ratio, the effect is practically marginal. It is not acceptable to use ACI 318 code spilt cylinder equation for plasticaggregate concrete with higher replacement ratioÂ Â